Method and Media of Health Promotion in Adolecents with Disability in Kupang City (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
Teenager with disability is unable to access health promotion service. This is due to the absence of method and special media of health promotion for disability teenager according to what they need. The purpose of this research was to know the appropriate method and media for disability teenager according their impairment. This research using qualitative approach with purposive sampling method. The informant in this research is taken from 8 disability teenager which are daksha, deaf/speech impairment and intelectual disability. The result shows that health topics that informant need to know is reproductive health, hygiene and health life style. The communicators of health topics selected by informants are healthy staff and teacher. Methods and media selected by informants are based on their impairment: teenager with daksha disability choose the method of disscussion and playing games with the media learning in the form of moving image; teenager with intelectual disability choose a method of sharing and disscussion with media learning in the form of illustrated books and moving image (film/video); deaf/speech impaired teenager didn’t choose any spesific methods., but they asked to use the sign language in delivery the information. The selection method health promotion have to involve teenager with disability. In planning health promotion methods and media for teenager with disability have to involve teacher and/or their parent, who know and understand the needs of each disable teenager.